Freeze Vacuum Drying With Utilized Waste Heat of Condenser by Quick Drying Method - Martin, Awaludin; Prayetno, Utari; Wahyudi, Wandi; Kurniawan, Iwan; , Romy (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Freeze vacuum drying process is an optimum process to dry the product without changing the physical and chemical properties of materials. The advantages of drying with freeze vacuum drying are can be maintain the structures, nutrient, and colors of original substances. A weakness of freeze vacuum drying is its high consumption of energy due to the long drying time required especially in the process of sublimation below triple point condition. The aim of this research areto optimizing freeze vacuum drying in order to reducing energy consumption by utilized waste heat of condenser to speed up the sublimation process and by using quick drying method. Thefreezing temperatures in this study were 6° C and 9° C with a variation of the drying time is 1, 2 and 4 hours. This research was result the water content losses in yam bean are 78% at a freeze temperature -9° C with drying time 4 hours.